Mucormycosis: the black fungus maiming COVID-19 patients in India - Ghogre, Priyanka (International Journal of Research in Medical Sciences, 2021)
The COVID-19 infection caused by the novel SARS-CoV-2 may be associated with a wide range of disease patterns, ranging from mild to life-threatening pneumonia. Mucormycosis is an emerging angioinvasive fungal infection caused by the ubiquitous filamentous fungi of the Mucorales order of the class of Zygomycetes. The prevalence of mucormycosis in India is about 80 times the prevalence in developed countries. Mucorales invade deep tissues via inhalation of airborne spores, percutaneous inoculation or ingestion. Rhino-orbito-cerebral form of mucormycosis is a relatively fatal infection and mortality rate rises to 50-85%. Extensive use of corticosteroids/monoclonal antibodies/broad-spectrum antibiotics may lead to the development/exacerbation of a preexisting fungal disease. Only amphotericin B and its lipid formulations and recently isavuconazole have been studied as first-line therapy for mucormycosis. On the contrary, posaconazole has been mainly studied as salvage therapy.